PENERAPAN MODEL PEMBELAJARAN PBL YANG DIKOMBINASIKAN DENGAN MEDIA ENSIKLOPEDIA DAN LKPD UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA SMP NEGERI 3 WAINGAPU - Rambu Yawu, Ningsi; Tamu Ina, Anita; Louise Makatita, Audrey (Jurnal Biogenerasi, 2024)
This research was conducted to determine the improvement in student learning outcomes by using the Problem Based Learning learning model assisted by Encyclopedia Media and LKPD to improve student learning outcomes at SMP Negeri 3 Waingapu. This type of research is Classroom Action Research (PTK), with a descriptive quantitative approach. In this study, class VIII F was used because the SAS results were the lowest. This research used a sample of 28 students. Learning outcomes in the cognitive domain are obtained from pretest and posttest scores and affective assessments. Student learning outcomes were analyzed using Microsoft Excel analysis. The results of the research showed that the average pre-cycle learning outcome was 46.80, whereas in cycle I there was a slight increase although not optimal with an average value of 59.14 and in cycle II there was an increase of 72.14. The percentage of students who achieved the KKTP in the pre-cycle was 20%, in the first cycle there were 46% who achieved completeness, while in the second cycle it increased and reached 86%. The results of the students' affective assessment in the first cycle were 33% and in the second cycle the category was. 83%, which was the highest category. The conclusion obtained from this research is that the application of the Problem Based Learning learning model assisted by Encyclopedia Media and LKPD can improve student